2022
DOI: 10.1002/aic.17817
|View full text |Cite
|
Sign up to set email alerts
|

Predictive control of particlesize distribution of crystallization process using deep learning based image analysis

Abstract: The challenges to regulate the particle‐size distribution (PSD) stem from on‐line measurement of the full distribution and the distributed nature of crystallization process. In this article, a novel nonlinear model predictive control method of PSD for crystallization process is proposed. Radial basis function neural network is adopted to approximate the PSD such that the population balance model with distributed nature can be transformed into the ordinary differential equation (ODE) models. Data driven nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…The average detection time floated slightly around 10 s, and the fixed average detection time indicated that the computational costs of Mask R‐CNN would not fluctuate severely with image qualities. However, compared to the related work, the processing speed of Mask R‐CNN still needs to be improved to meet the requirements of process control 15 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average detection time floated slightly around 10 s, and the fixed average detection time indicated that the computational costs of Mask R‐CNN would not fluctuate severely with image qualities. However, compared to the related work, the processing speed of Mask R‐CNN still needs to be improved to meet the requirements of process control 15 …”
Section: Resultsmentioning
confidence: 99%
“…14 Moreover, the processing speed of image-based ANN can satisfy the process control requirements of solution crystallization. Wang et al proposed a novel nonlinear model predictive control method for the crystallization process using deep-learning based image analysis technology as an online monitoring tool for CSD 15 control. Different types of ANNs have a wide range of capabilities for the analysis of crystal microscopic images.…”
Section: Introductionmentioning
confidence: 99%
“…Anandan et al developed a controller based on reinforcement learning and applied it to the crystallization of paracetamol to achieve the desired crystal size . Machine learning approaches have also been used to control crystallization processes based on image analysis. Furthermore, many applications in the literature propose hybrid modeling approaches that use neural networks combined with the population balance. …”
Section: Introductionmentioning
confidence: 99%